The impact of perceived price justice and satisfaction on customer loyalty towards restaurant industry - Saputro, Faris Hani; Supardi; Hasim, Muhammad Asyraf (International Journal of Psychosocial Rehabilitation, 2020)
This study is about the perceived price justice towards customer loyalty with the customer satisfaction as the mediator. The role of pricing is crucial in today business especially when there are too many competitors in the industry. Restaurant is a kind of business that have a huge threat in rivalry among industry members. Restaurant also facing a well-informed customer where they have more knowledge and access to information. Data were collected from a selected prominent restaurant located in major cities in Indonesia. 200 respondents participated in the survey that have been done over 7 days during peak and off-peak hours. The survey was assisted by 5 research assistant that will approach customer at the restaurant compounds after they has finished their meals. The findings revealed that both that both perceived price justice and customer satisfaction have a positive relationship towards customer loyalty. Customer satisfaction at the same time become the predictors and control variable that hold a positive relationship for both parts. This study is important as it was done during the right time where the competition is stiff and customer are more knowledgeable. The fast development of technology has led to a more access to information online. Customer know exactly where there can have good meals and able to compare or read the review before making decision.